A Study to Assess the Effectiveness of Buerger Allen Exercise in Improving the Peripheral Circulation among Patients with Diabetes Mellitus Admitted in Sharda Hospital, Greater Noida (International Journal of Nursing Education, 2019)
Diabetes as one of Non-communicable diseases has consumed a large share of money, material, time and human resources of health systems. Now, due to advancement in lifestyle and industrial process, prevalence of diabetes and its associated complications have been raised. Among these complications, diabetic foot considered as a common complication of diabetes. Nurses as a health care providers has a responsibility for prevention and early diagnoses of diabetes and its complications.1 A study was conducted to assess the effectiveness of Buerger Allen Exercise in improving the peripheral circulation among patients with diabetes mellitus admitted in Sharda Hospital, Greater Noida The research approach adopted for this study was quantitative research approach and Quasi-experimental pre- test and post-test control group was research design.There were 60 Patients admitted with diabetes mellitus selected by using simple random sampling technique and were randomly allocated in experimental and control group using lottery method. The correlation coefficient was 0.86. The results showed that from baseline to after 20 minutes of Buerger allen exercise mean score become 2.56 to 1.4 in experimental group and mean difference Inlow’s score in experimental group were (1.1+0.017) is higher as compare to control group (0.2+0.005). it revealed that there was significant improvement in peripheral circulation after Buerger allen. This study showed that Buerger allen exercise become more effective along with hospital routine treatment in diabetic mellitus patient. Buerger allen exercise can be used for improvement in peripheral circulation among Diabetes mellitus patients
Keywords: Buerger allen exercise, Effective, Diabetic mellitus patient, Peripheral circulation